Peningkatan Kemampuan Penyusunan Laporan Keuangan Sesuai Standar Akuntansi bagi Pelaku UMKM di Provinsi Banten - Iis Solihat; Pesi Suryani; Olivia Idrus; Any Meilani; Amalia Kusuma Wardini (Penerbit Goodwood, 2022)
Purpose: Community service activity by Lecturers of Accounting Study Program of Universitas Terbuka (UT) aims to provide training for the community of Micro, Small, and Medium Enterprises (MSMEs) in making financial reports in accordance with accounting standards for MSMEs. This is conducted to solve the problems faced by MSMEs who still have a lot of difficulties in recording and reporting financial statements, which ultimately has an impact on the difficulty of obtaining credit from financial institutions. Method: This activity was attended by MSMEs from Banten Province and consisted of several stages, namely (1) planning, through discussions with MSMEs, (2) presentation from speakers, answering questions and discussions through web seminars in the Zoom application as well as live streaming in UT's youtube channel and (3) mentoring the making of financial reports to five participants who answered the quiz. Result: The results of community service activities show that MSMEs are able to enable the preparation of SAK ETAP MSME financial statements in the form of general journals, adjustment journals, ledgers, balance sheets, working papers, income statements of MSME actors ready to develop and successfully get capital assistance from financial institutions. Conclusion: This exercise is highly valuable for participants and stimulates them, according to the comments received from them. And it is believed that with the help of financial statements, banks, and non-bank financial institutions would be able to give loans to MSMEs.